PENGEMBANGAN KESENIAN KEMPLING SEBAGAI UPAYA PELESTARIAN DI DESA WISATA KANDRI KOTA SEMARANG - Raharjo, Aprellian Luthfi; Muttaqin, Moh.; Rachman, Abdul (Indonesian Journal of Conservation, 2018)
Kempling art is a traditional art that has the characteristics of the form of musical performances that use musical instruments gembur, kendhang, karon, telon, kempling and kemanak which is almost the same as the tools used in rebana music which in its development changed like the addition of a keyboard and guitar that is not leaving the characteristic Kempling art with songs that sung like sholawatan, praise and songs that are poupuler in society. Kempling art is an art that has existed in the era of Sunan Giri and Sunan Kalijaga and in 1962 preserved in the Village Tourism Kandri Semarang City. Kempling Art Development conducted by Kempling Art Group is done so that Kempling Art can be enjoyed by the people of Semarang City. Kandri Tourism Village becomes a tourist village in 2012 and it becomes the community's duty to manage and utilize the existing tourism potentials. This study uses qualitative methods with data collection techniques using observation, interviews and documentation and data validity techniques examined by source triangulation method. The purpose of the study is to describe the development undertaken by the community without changing and keep holding tightly Kempling Artistry in the Village Kandri Semarang. Kempling art development is done through the development of songs, musical instruments, performances and costumes.